Self-repairing long-acting anticorrosive coating material as well as preparation method and application thereof

By optimizing the ratio and preparation process of nanofillers, bio-based polyurethanes and microcapsules, the existing self-repair anticorrosion coatings have been solved, and the long-term self-repair function and environmentally friendly production of the coating have been achieved, which significantly improves the market competitiveness and sustainability of the products.

CN119505678AInactive Publication Date: 2025-02-25SHANDONG VOSGES XUANWEI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510052929.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing self-repair anticorrosion coatings have problems such as high production costs, poor performance stability, complex preparation process, threats to the environment and human health using organic solvents, and improper waste treatment may cause secondary pollution.

Method used

By optimizing the ratio and preparation process of nanofillers, bio-based polyurethanes and microcapsules, the mechanical properties, self-repair capabilities and corrosion resistance of the coating are significantly improved, and environmentally friendly preparation methods are adopted to reduce the use of organic solvents and reduce production costs.

Benefits of technology

It realizes the long-term self-repair function of the coating, significantly extends the service life, reduces maintenance frequency and cost, and improves the environmental protection and market competitiveness of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a self-repairing long-acting anticorrosive coating material as well as a preparation method and application thereof, and relates to the technical field of anticorrosive paint preparation. The coating material is prepared from the following raw materials in parts by mass: 50 to 70 parts of bio-based polyurethane, 10 to 20 parts of microcapsules, 5 to 15 parts of nano filler and 5 to 10 parts of auxiliaries, according to the microcapsule, an isocyanate mixture serves as a core material, hexamethylene diisocyanate serves as a wall material, and the isocyanate mixture comprises a prepolymer generated through a reaction of lignin and hydrogenated xylylene diisocyanate and excessive hydrogenated xylylene diisocyanate in the reaction. The method for preparing the self-repairing long-acting anti-corrosion coating material is simple and convenient to operate and easy for industrial production, can remarkably improve the anti-corrosion performance of the base material, reduce the maintenance cost and prolong the service life in practical application, and has a wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-corrosion coating preparation, and in particular to a self-repairing long-acting anti-corrosion coating material and a preparation method and application thereof. Background Art

[0002] As the global awareness of environmental protection and sustainable development continues to increase, the development of environmentally friendly products, especially materials in the industrial field, has become one of the important trends in today's society. Among many industrial materials, anti-corrosion coatings have attracted much attention due to their wide range of applications. Traditional anti-corrosion coatings are mainly made of petroleum-based materials. Although these materials have excellent anti-corrosion properties, they consume a large amount of non-renewable resources during their production and use, and may release harmful substances such as volatile organic compounds (VOCs) and heavy metals, posing a potential threat to the environment and human health.

[0003] In view of the above problems, the development of new environmentally friendly anti-corrosion coatings has become a research hotspot in recent years. Among them, self-healing anti-corrosion coatings based on bio-based materials are particularly valued. Bio-based materials come from renewable resources such as vegetable oils, starch, cellulose, etc. The use of these materials can not only reduce dependence on fossil fuels, but also help reduce carbon emissions in the production process and reduce pressure on the environment. In addition, by giving these materials self-healing functions through specific technical means, the service life of the coating can be effectively extended, further improving the sustainability of the material.

[0004] The working principle of self-healing anti-corrosion coatings usually involves two mechanisms: one is that the internally stored repair agent is automatically released when damage occurs, reacting with air or moisture to form a new protective layer; the other is to use the chemical or physical properties of the material itself to spontaneously restore the damaged part under external stimulation. Both mechanisms can reduce maintenance costs to a certain extent and improve the safety and reliability of facilities.

[0005] In summary, the development of self-healing anti-corrosion coatings based on bio-based materials not only promotes the green transformation of the coatings industry, but also provides technical support for the sustainable development of the social economy. However, such products currently have the following major problems on the market: 1) High production costs, which limits market competitiveness; 2) Poor performance stability in extreme environments, which affects long-term use effects; 3) Complex preparation processes, which increase production difficulty and costs; 4) The use of organic solvents poses a threat to the environment and human health; 5) Improper waste disposal may cause secondary pollution.

[0006] Therefore, the present invention aims to provide an efficient, environmentally friendly and economically feasible self-repairing anti-corrosion coating solution to overcome the shortcomings of the prior art. Summary of the invention

[0007] In view of this, the present invention proposes a self-repairing long-term anti-corrosion coating material and its preparation method and application. By optimizing the ratio and preparation process of nanofillers, bio-based polyurethane and microcapsules, the mechanical properties, self-repairing ability and corrosion resistance of the coating are significantly improved. At the same time, an environmentally friendly preparation method is adopted, the use of organic solvents is reduced, the production cost is reduced, and the market competitiveness of the product is improved.

[0008] In a first aspect, the present invention provides a self-repairing long-lasting anti-corrosion coating material, which comprises the following raw materials by weight: 50-70 parts of bio-based polyurethane, 10-20 parts of microcapsules, 5-15 parts of nanofillers and 5-10 parts of additives; The microcapsule uses an isocyanate mixture as a core material and hexamethylene diisocyanate as a wall material. The isocyanate mixture includes a prepolymer generated by the reaction of lignin and hydrogenated xylylene diisocyanate and excess hydrogenated xylylene diisocyanate in the reaction.

[0009] The bio-based polyurethane of this application helps to ensure the basic performance of the coating. The design of the microcapsules can realize the self-repair function of the coating: when the coating is damaged, the microcapsules rupture to release the core material, and the core material reacts with moisture or other substances in the air to form a protective layer, thereby achieving a self-repairing effect, which can not only extend the service life of the coating, but also reduce maintenance costs. The addition of nanofillers can significantly improve the physical and chemical properties of the coating, such as enhancing the hardness, wear resistance and corrosion resistance of the coating. In addition, nanofillers can also improve the adhesion of the coating, making it fit more closely to the surface of the substrate.

[0010] By adopting the above technical solution, the synergistic effect of microcapsule technology and nanofillers can make the coating automatically repair itself when damaged, restoring its integrity and protective function; the combination of bio-based polyurethane and nanofillers also gives the coating excellent corrosion resistance, ensuring that the coating maintains a good protective effect for a long time. The self-healing long-lasting anti-corrosion coating material of this application can not only significantly extend the service life of the coating and improve the anti-corrosion performance through its unique composition design, but also has good environmental protection and economy, meets the environmental protection requirements of sustainable development, and has broad application prospects.

[0011] Furthermore, the bio-based polyurethane is plant oil-based polyurethane.

[0012] On the basis of the above technical scheme, in the plant oil-based polyurethane, the plant oil is selected from soybean oil, rapeseed oil, palm oil, castor oil or waste oil; the preparation of the plant oil-based polyurethane comprises the following steps: using oxide to modify the plant oil to obtain epoxy plant oil; and then adding isocyanate to obtain the plant oil-based polyurethane.

[0013] On the basis of the above technical solution, the oxide is selected from one or more of hydrogen peroxide, peracid or persulfate, and the present invention preferably uses a hydrogen peroxide solution with a mass content of 30%.

[0014] Based on the above technical solution, the molar ratio of the vegetable oil to the hydrogen peroxide solution is 1:1.5.

[0015] On the basis of the above technical solution, the isocyanate is selected from toluene diisocyanate and / or diphenylmethane diisocyanate.

[0016] On the basis of the above technical solution, preferably, the molar ratio of the epoxy vegetable oil to the isocyanate is 1:1.

[0017] Furthermore, the average particle size of the microcapsules does not exceed 10 μm, and the shell thickness is 1.2±0.25 μm.

[0018] Furthermore, in the microcapsule, the mass ratio of the core material to the wall material is 1:1 to 3:1.

[0019] By adopting the above technical solution, a core material ratio that is too high may result in insufficient wall material to completely wrap the core material, thereby affecting the structural integrity and sealing of the microcapsule, which may cause leakage or uncontrolled release rate. A low core material ratio helps to improve the stability of the microcapsule and control the release rate, but may lead to a decrease in self-healing ability.

[0020] Furthermore, in the isocyanate mixture, the mass ratio of the lignin to hydrogenated xylylene diisocyanate is 1:1.5 to 1:2.

[0021] By adopting the above technical solution, a moderate cross-linking density is ensured, which not only enhances the mechanical strength and chemical stability of the microcapsule wall, but also maintains a certain flexibility, avoiding the problem of the shell being too rigid or too thin, thereby ensuring the ideal shell thickness and encapsulation efficiency. In addition, this ratio helps to reduce the occurrence of side reactions, reduce the risk of residual unreacted isocyanate groups, and ensure the stability and durability of the final product. Too high a ratio will lead to excessive cross-linking, making the microcapsule wall too rigid, stress concentration and may cause unnecessary side reactions; while too low a ratio will weaken the degree of cross-linking, reduce mechanical strength and thermal stability, and affect encapsulation efficiency and release behavior.

[0022] Furthermore, the average particle size of the nanofiller is 10-100 nm, and the nanofiller is selected from nanocellulose and / or nanosilicon dioxide.

[0023] On the basis of the above technical solution, the nano filler is a mixture of nano cellulose and nano silicon dioxide in any ratio.

[0024] Preferably, the mass ratio of the nano-cellulose to the nano-silicon dioxide is 0.6-1.5:1.

[0025] By adopting the above technical solutions and rationally selecting and matching nanofillers of different particle sizes, the comprehensive performance of self-healing long-term anticorrosion coatings based on bio-based and microencapsulation technology can be significantly improved. The multi-scale filling structure of nanocellulose and nanosilica not only improves the mechanical properties and corrosion resistance of the coating, but also enhances the self-healing effect, ensuring that the coating performs well in a variety of application fields and meets the requirements of long-term repair.

[0026] Furthermore, the auxiliary agent, by weight, includes 1 to 3 parts of ultraviolet absorber, 1 to 3 parts of antioxidant and 1 to 4 parts of plasticizer.

[0027] More preferably, the ultraviolet absorber is UV-326, the antioxidant is TTO (tea tree oil), and the plasticizer is DOP (dioctyl phthalate).

[0028] By adopting the above technical solutions, UV-326 is a highly efficient UV absorber that can effectively absorb ultraviolet rays and prevent the coating from aging and degradation due to ultraviolet radiation, thereby extending the service life of the coating. Tea tree oil not only has excellent antioxidant properties, which can prevent lipid oxidation in the material and delay the aging process, but also has a broad-spectrum antibacterial effect, which can inhibit the growth of a variety of bacteria and fungi, and reduce the risk of biofouling and microbial-induced corrosion. Dioctyl phthalate (DOP) as a plasticizer can improve the flexibility and processing properties of the coating, making it easier to operate in application and maintaining good mechanical properties. This combination not only enhances the weather resistance and protective properties of the coating, but also improves its antibacterial and anti-aging capabilities, ensuring that the coating maintains a good appearance and function for a long time, and is suitable for applications in various harsh environments.

[0029] Furthermore, the additives also include a leveling agent, a defoaming agent, a suspending agent, and a solvent for adjusting the viscosity of the coating.

[0030] On the basis of the above technical solution, according to the requirements of practical application, the solvent can be selected from a diluent or a thickener; the diluent is selected from ethanol, acetone or water, and the thickener is selected from hydroxyethyl cellulose or xanthan gum.

[0031] In a second aspect, the present invention relates to a method for preparing the above-mentioned self-repairing long-lasting anti-corrosion coating material, comprising the following steps: Step 1: Preparation of microcapsules Under stirring conditions, prepolymerizing lignin and hydrogenated xylylene diisocyanate according to a mass ratio at 80-90° C. to obtain an isocyanate mixture, and after cooling, adding hexamethylene diisocyanate to the isocyanate mixture to obtain an oil phase; adding the oil phase to an aqueous solution of a surfactant under an ice bath, stirring to obtain a stable emulsion, then adding an amine curing agent, heating to 40-60° C. and keeping the temperature for 2-4 hours, filtering, washing, and drying to obtain microcapsules; Step 2: Prepare coating materials The bio-based polyurethane, microcapsules, nanofillers and additives are sequentially mixed according to the mass fractions, stirred, filtered, and the coating material is prepared.

[0032] By adopting the above technical solution, firstly, the microcapsules prepared by the method contain a repair agent, which can automatically release the repair agent when the coating is damaged, thereby realizing the self-repair function of the coating. This self-repair property can significantly extend the service life of the coating, reduce the maintenance frequency, reduce the long-term use cost, and improve the durability of the protected material. Secondly, the preparation method of the coating material of the present invention is simple and easy to operate, while ensuring sufficient mixing between the components.

[0033] In the present invention, the preparation of microcapsules utilizes an isocyanate mixture (HMDI-PU prepolymer and HMDI mixture) formed by lignin and excess hydrogenated benzyl diisocyanate (HMDI) at a certain temperature, and then uses interfacial polymerization technology to encapsulate the isocyanate mixture in a microcapsule shell composed of hexamethylene diisocyanate (HDI).

[0034] Based on the above scheme, preferably, the volume ratio of the oil phase to the aqueous solution of the surfactant is 4:1.

[0035] More preferably, the aqueous solution of the surfactant is a 1 wt % aqueous solution of sodium lignin sulfonate.

[0036] Furthermore, in step 2, the stirring process includes 10 to 20 minutes at 200 to 500 r / min and 30 to 60 minutes at 1000 to 2000 r / min.

[0037] In the present invention, the viscosity of the self-repairing long-acting anti-corrosion coating material of the present invention can be adjusted according to different actual construction processes.

[0038] On the third aspect, the present application provides the application of the above-mentioned self-repairing long-lasting anti-corrosion coating material in the fields of marine engineering, chemical equipment, building exterior walls and transportation.

[0039] The self-repairing long-lasting anti-corrosion coating material provided by the present invention has the following beneficial effects compared with the prior art: 1. The self-repairing long-lasting anti-corrosion coating material of the present invention, with bio-based polyurethane as the main component, not only provides excellent mechanical properties and chemical stability, but also has excellent self-repairing ability. The addition of microcapsules can automatically release repair agents when tiny cracks appear in the coating, quickly restoring the integrity and protective performance of the coating. This self-repairing mechanism significantly extends the service life of the coating and reduces maintenance frequency and cost.

[0040] 2. The coating material of the present invention further enhances the hardness, wear resistance and corrosion resistance of the coating by using nanofillers. The high specific surface area and surface activity of the nanofillers form physical crosslinking points in the coating, which improves the mechanical strength and toughness of the coating, and forms a dense barrier to effectively block the penetration of corrosive media. Its synergistic effect with bio-based polyurethane and microcapsules ensures the stability and durability of the coating in long-term use, and significantly improves the anti-corrosion performance of the substrate.

[0041] 3. The method for preparing a self-repairing long-lasting anti-corrosion coating material of the present invention is simple to operate and easy to industrialize. In practical applications, it can significantly improve the anti-corrosion performance of the substrate, reduce maintenance costs, and extend service life, and has broad market application prospects. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of the materials mainly involved in the examples are shown in Table 1 below, and the remaining materials not shown are conventional commercial products.

[0044] Table 1 Material source description

[0045] The following are preparation examples of the present application, and preparation examples 1 to 4 provide a microcapsule respectively.

[0046] Preparation Example 1 The microcapsules of this preparation example are obtained by the following steps: S1. Preparing an isocyanate mixture: mixing lignin and hydrogenated xylylene diisocyanate at a mass ratio of 1:1.8 at 90° C. under stirring to prepare an isocyanate mixture; S2. preparing an oil phase: mixing the isocyanate mixture obtained in step S1 and hexamethylene diisocyanate in a mass ratio of 1:1 to obtain an oil phase; S3. Preparation of microcapsules: In an ice bath, add a 1 wt % aqueous solution of sodium lignin sulfonate (aqueous phase) into a flask, then add the oil phase of step S2 into the flask, wherein the volume ratio of the aqueous phase to the oil phase is 1:4, stir at 500 rpm to obtain a stable emulsion, then add an aqueous solution of ethylenediamine in an equimolar amount to the isocyanate group, heat to 60° C. and keep warm for 2 h, cool to room temperature, filter, wash, and dry to obtain microcapsules with a shell thickness of 1.35 μm.

[0047] Preparation Example 2 The microcapsules of this preparation example are obtained by the following steps: S1. Preparing an isocyanate mixture: mixing lignin and hydrogenated xylylene diisocyanate at a mass ratio of 1:1.5 at 85° C. under stirring to prepare an isocyanate mixture; S2. preparing an oil phase: mixing the isocyanate mixture obtained in step S1 and hexamethylene diisocyanate in a mass ratio of 1:1 to obtain an oil phase; S3. Preparation of microcapsules: In an ice bath, add a 1 wt % aqueous solution of sodium lignin sulfonate (aqueous phase) into a flask, then add the oil phase of step S2 into the flask, wherein the volume ratio of the aqueous phase to the oil phase is 1:4, stir at 500 rpm to obtain a stable emulsion, then add an aqueous solution of ethylenediamine in an equimolar amount to the isocyanate group, heat to 40° C. and keep warm for 6 h, cool to room temperature, filter, wash, and dry to obtain microcapsules with a shell thickness of 1.25 μm.

[0048] Preparation Example 3 The microcapsules of this preparation example are obtained by the following steps: S1. Preparing an isocyanate mixture: mixing lignin and hydrogenated xylylene diisocyanate at a mass ratio of 1:1.5 at 85° C. under stirring to prepare an isocyanate mixture; S2. preparing an oil phase: mixing the isocyanate mixture obtained in step S1 and hexamethylene diisocyanate in a mass ratio of 1:1 to obtain an oil phase; S3. Preparation of microcapsules: In an ice bath, add a 1 wt % aqueous solution of sodium lignin sulfonate (aqueous phase) into a flask, then add the oil phase of step S2 into the flask, wherein the volume ratio of the aqueous phase to the oil phase is 1:4, stir at 500 rpm to obtain a stable emulsion, then add an aqueous solution of ethylenediamine in an equimolar amount to the isocyanate group, heat to 50° C. and keep warm for 3 h, cool to room temperature, filter, wash, and dry to obtain microcapsules with a shell thickness of 1.20 μm.

[0049] Preparation Example 4 The microcapsules of this preparation example are obtained by the following steps: S1. Preparing an isocyanate mixture: mixing lignin and hydrogenated xylylene diisocyanate at a mass ratio of 1:2 at 80° C. under stirring to prepare an isocyanate mixture; S2. preparing an oil phase: mixing the isocyanate mixture obtained in step S1 and hexamethylene diisocyanate in a mass ratio of 1:1 to obtain an oil phase; S3. Preparation of microcapsules: In an ice bath, add a 1 wt % aqueous solution of sodium lignin sulfonate (aqueous phase) into a flask, then add the oil phase of step S2 into the flask, wherein the volume ratio of the aqueous phase to the oil phase is 1:4, stir at 500 rpm to obtain a stable emulsion, then add an aqueous solution of ethylenediamine in an equimolar amount to the isocyanate group, heat to 50° C. and keep warm for 2 h, cool to room temperature, filter, wash, and dry to obtain microcapsules with a shell thickness of 1.45 μm.

[0050] Preparation Examples 5 to 8 each provide a bio-based polyurethane.

[0051] Preparation Example 5 The bio-based polyurethane of this preparation example is obtained by the following steps: S1. Preparation of epoxidized vegetable oil: Slowly add 150 g of 30% hydrogen peroxide solution to 100 g of soybean oil, stir at a speed of 500 r / min, and react at 60° C. for 2 hours to form epoxidized soybean oil; S2. Preparation of soybean oil-based polyurethane: 100 g of toluene diisocyanate was slowly added to 100 g of epoxidized soybean oil, the mixture was stirred at a speed of 800 r / min, and the mixture was reacted at 80° C. for 3 hours to form a soybean oil-based polyurethane.

[0052] Preparation Example 6 The bio-based polyurethane of this preparation example is obtained by the following steps: S1. Preparation of epoxidized vegetable oil: Slowly add 150 g of 30% hydrogen peroxide solution to 100 g of rapeseed oil, stir at a speed of 500 r / min, and react at 60° C. for 2 hours to form epoxidized rapeseed oil; S2, preparation of rapeseed oil-based polyurethane: 100 g of diphenylmethane diisocyanate was slowly added to 100 g of epoxy rapeseed oil, stirred at a speed of 800 r / min, and reacted at 80 ° C for 3 hours to form rapeseed oil-based polyurethane.

[0053] Preparation Example 7 The bio-based polyurethane of this preparation example is obtained by the following steps: S1. Preparation of epoxidized vegetable oil: Slowly add 150 g of 30% hydrogen peroxide solution to 100 g of palm oil, stir at a speed of 500 r / min, and react at 60° C. for 2 hours to form epoxidized palm oil; S2. Preparation of palm oil-based polyurethane: 100 g of diphenylmethane diisocyanate was slowly added to 100 g of epoxy palm oil, stirred at a speed of 800 r / min, and reacted at 80° C. for 3 hours to form palm oil-based polyurethane.

[0054] Preparation Example 8 The bio-based polyurethane of this preparation example is obtained by the following steps: S1. Preparation of epoxidized vegetable oil: Slowly add 150 g of 30% hydrogen peroxide solution to 100 g of waste oil, stir at a speed of 500 r / min, and react at 60° C. for 2 hours to form epoxidized waste oil; S2, preparation of waste grease-based polyurethane: 100 g of diphenylmethane diisocyanate was slowly added to 100 g of epoxy waste grease, stirred at a speed of 800 r / min, and reacted at 80 ° C for 3 hours to form a waste grease-based polyurethane.

[0055] Example 1 The present embodiment provides a self-repairing long-lasting anti-corrosion coating material, comprising the following raw materials: 50 grams of the bio-based polyurethane of Preparation Example 5, 10 grams of the microcapsules of Preparation Example 1, 5 grams of nanocellulose and 5 grams of additives (1 gram of UV absorber, 1 gram of antioxidant, 2 grams of plasticizer, and the remainder is leveling agent and defoaming agent).

[0056] The self-repairing long-lasting anti-corrosion coating material of this embodiment is prepared by the following steps: The above raw materials were mixed in sequence, first stirred at 200 r / min for 10 minutes, and then stirred at 1000 r / min for 30 minutes to ensure that the components were fully mixed. The mixed coating was filtered through a filter to remove possible impurities or incompletely dispersed particles to ensure the smoothness and quality of the coating, so as to obtain a self-repairing long-lasting anti-corrosion coating material.

[0057] Example 2 The present embodiment provides a self-repairing long-lasting anti-corrosion coating material, comprising the following raw materials: 65 grams of the bio-based polyurethane of Preparation Example 6, 15 grams of the microcapsules of Preparation Example 2, 10 grams of nanofiller (6 grams of nanocellulose, 4 grams of nanosilica) and 10 grams of additives (1.5 grams of ultraviolet absorber, 1.5 grams of antioxidant, 2.5 grams of plasticizer, and the remainder is leveling agent and defoaming agent).

[0058] The self-repairing long-lasting anti-corrosion coating material of this embodiment is prepared by the following steps: The above raw materials were mixed in sequence, first stirred at 300 r / min for 15 minutes, and then stirred at 1500 r / min for 45 minutes to ensure that the components were fully mixed. The mixed coating was filtered through a filter to remove possible impurities or incompletely dispersed particles to ensure the smoothness and quality of the coating, so as to obtain a self-repairing long-lasting anti-corrosion coating material.

[0059] Example 3 The present embodiment provides a self-repairing long-lasting anti-corrosion coating material, comprising the following raw materials: 65 grams of the bio-based polyurethane of Preparation Example 7, 18 grams of the microcapsules of Preparation Example 3, 13 grams of nanofillers (6.5 grams of nanocellulose, 6.5 grams of nanosilica) and 8 grams of additives (1.5 grams of ultraviolet absorber, 1.5 grams of antioxidant, 2.5 grams of plasticizer, and the remainder is leveling agent and defoaming agent).

[0060] The self-repairing long-lasting anti-corrosion coating material of this embodiment is prepared by the following steps: The above raw materials were mixed in sequence, first stirred at 300 r / min for 15 minutes, and then stirred at 1500 r / min for 45 minutes to ensure that the components were fully mixed. The mixed coating was filtered through a filter to remove possible impurities or incompletely dispersed particles to ensure the smoothness and quality of the coating, so as to obtain a self-repairing long-lasting anti-corrosion coating material.

[0061] Example 4 The present embodiment provides a self-repairing long-lasting anti-corrosion coating material, comprising the following raw materials: 70 grams of the bio-based polyurethane of Preparation Example 8, 20 grams of the microcapsules of Preparation Example 4, 15 grams of nanofillers (7 grams of nanocellulose, 8 grams of nanosilica) and 10 grams of additives (2 grams of ultraviolet absorber, 2 grams of antioxidant, 3 grams of plasticizer, and the remainder is leveling agent and defoaming agent).

[0062] The self-repairing long-lasting anti-corrosion coating material of this embodiment is prepared by the following steps: The above raw materials were mixed in sequence, first stirred at 500 r / min for 20 minutes, and then stirred at 2000 r / min for 60 minutes to ensure that the components were fully mixed. The mixed coating was filtered through a filter to remove possible impurities or incompletely dispersed particles to ensure the smoothness and quality of the coating, so as to obtain a self-repairing long-lasting anti-corrosion coating material.

[0063] Example 5 The present embodiment provides a self-repairing long-lasting anti-corrosion coating material, comprising the following raw materials: 60 grams of the bio-based polyurethane of Preparation Example 5, 15 grams of the microcapsules of Preparation Example 1, 8 grams of nanofiller (3 grams of nanocellulose, 5 grams of nanosilica) and 10 grams of additives (2 grams of ultraviolet absorber, 2 grams of antioxidant, 3 grams of plasticizer, and the remainder is leveling agent and defoaming agent).

[0064] The self-repairing long-lasting anti-corrosion coating material of this embodiment is prepared by the following steps: The above raw materials were mixed in sequence, first stirred at 400 r / min for 15 minutes, and then stirred at 1500 r / min for 40 minutes to ensure that the components were fully mixed. The mixed coating was filtered through a filter to remove possible impurities or incompletely dispersed particles to ensure the smoothness and quality of the coating, so as to obtain a self-repairing long-lasting anti-corrosion coating material.

[0065] Example 6 The present embodiment provides a self-repairing long-lasting anti-corrosion coating material, comprising the following raw materials: 60 grams of the bio-based polyurethane of Preparation Example 5, 15 grams of the microcapsules of Preparation Example 1, 15 grams of nanofillers (5 grams of nanocellulose, 10 grams of nanosilica) and 10 grams of additives (2 grams of ultraviolet absorber, 2 grams of antioxidant, 3 grams of plasticizer, and the remainder is leveling agent and defoaming agent).

[0066] The self-repairing long-lasting anti-corrosion coating material of this embodiment is prepared by the following steps: The above raw materials were mixed in sequence, first stirred at 400 r / min for 15 minutes, and then stirred at 1500 r / min for 40 minutes to ensure that the components were fully mixed. The mixed coating was filtered through a filter to remove possible impurities or incompletely dispersed particles to ensure the smoothness and quality of the coating, so as to obtain a self-repairing long-lasting anti-corrosion coating material.

[0067] Example 7 The present embodiment provides a self-repairing long-lasting anti-corrosion coating material, comprising the following raw materials: 60 grams of the bio-based polyurethane of Preparation Example 5, 15 grams of the microcapsules of Preparation Example 1, 13 grams of nanofillers (8 grams of nanocellulose, 5 grams of nanosilica) and 10 grams of additives (2 grams of ultraviolet absorber, 2 grams of antioxidant, 3 grams of plasticizer, and the remainder is leveling agent and defoaming agent).

[0068] The self-repairing long-lasting anti-corrosion coating material of this embodiment is prepared by the following steps: The above raw materials were mixed in sequence, first stirred at 400 r / min for 15 minutes, and then stirred at 1500 r / min for 40 minutes to ensure that the components were fully mixed. The mixed coating was filtered through a filter to remove possible impurities or incompletely dispersed particles to ensure the smoothness and quality of the coating, so as to obtain a self-repairing long-lasting anti-corrosion coating material.

[0069] Comparative Example 1 The difference from Example 1 is that the following raw materials are included: 50 grams of the bio-based polyurethane of Preparation Example 5, 10 grams of the microcapsules of Preparation Example 1 and 5 grams of additives (1 gram of ultraviolet absorber, 1 gram of antioxidant, 2 grams of plasticizer, and the balance is leveling agent and defoamer). The preparation steps are the same as those of Example 1.

[0070] Comparative Example 2 The difference from Example 2 is that the following raw materials are included: 65 g of epoxy resin E51, 15 g of microcapsules of Preparation Example 2, 10 g of nanofiller (6 g of nanocellulose, 4 g of nanosilicon dioxide) and 10 g of additives (1.5 g of ultraviolet absorber, 1.5 g of antioxidant, 2.5 g of plasticizer, and the balance is leveling agent and defoamer). The preparation steps are the same as those of Example 2.

[0071] Comparative Example 3 The difference from Example 2 is that the following raw materials are included: 65 g of epoxy resin E51, 15 g of microcapsules of Preparation Example 2, 10 g of auxiliary agents (1.5 g of ultraviolet absorber, 1.5 g of antioxidant, 2.5 g of plasticizer, and the rest is leveling agent and defoamer). The preparation steps are the same as those of Example 2.

[0072] Comparative Example 4 The difference from Example 2 is that the following raw materials are included: 65 g of epoxy resin E51, 10 g of nano filler (6 g of nano cellulose, 4 g of nano silicon dioxide) and 10 g of auxiliary agent (1.5 g of ultraviolet absorber, 1.5 g of antioxidant, 2.5 g of plasticizer, and the rest is leveling agent and defoamer). The preparation steps are the same as those of Example 2.

[0073] Comparative Example 5 The difference from Example 3 is that the following raw materials are included: 65 g of the bio-based polyurethane of Preparation Example 7, 13 g of nanofiller (6.5 g of nanocellulose, 6.5 g of nanosilicon dioxide) and 8 g of additives (1.5 g of ultraviolet absorber, 1.5 g of antioxidant, 2.5 g of plasticizer, and the balance is leveling agent and defoamer). The preparation steps are the same as those of Example 3.

[0074] Comparative Example 6 The difference from Example 3 is that the following raw materials are included: 65 grams of the bio-based polyurethane of Preparation Example 7 and 8 grams of additives (1.5 grams of ultraviolet absorber, 1.5 grams of antioxidant, 2.5 grams of plasticizer, and the rest are leveling agent and defoamer). The preparation steps are the same as those of Example 3.

[0075] Comparative Example 7 Epoxy resin E51 was directly used as the coating material.

[0076] The following performance tests were performed on the above Examples 1 to 7 and Comparative Examples 1 to 7, including: (1) Tensile strength and elongation at break The test was carried out in accordance with the relevant records in ASTM D638 (Standard Test Method for Tensile Properties of Plastics).

[0077] (2) Repair efficiency Create scratches or cracks on the coating surface, place the coating in a standard environment, and record the mechanical properties of the coating before and after repair (based on tensile strength). Repair efficiency = (performance after repair / performance before repair) × 100%.

[0078] (3) Repair time Start timing from the appearance of scratches or cracks until the coating surface recovers to a state without obvious damage. The repair process can be observed through an optical microscope and the repair time can be recorded. Specific operation: Start timing immediately after making a standard scratch or crack on the coating surface. Use an optical microscope to observe the changes on the coating surface and record them at regular intervals (such as 10 minutes). When the coating surface recovers to a state without obvious damage, stop timing and record the repair time.

[0079] (4) Corrosion resistance The test was carried out according to the relevant records in ASTM B117 salt spray test.

[0080] (5) Stability The test was conducted in accordance with ASTM D2565 (Standard Practice for Xenon Arc Exposure of Plastics for Outdoor Use).

[0081] (6) Release rate This is done in accordance with the relevant documentation in ISO 10993-18 (Biological evaluation of medical devices - Part 18: Chemical characterization of materials).

[0082] The above test results are recorded in Table 2 below.

[0083] Table 2 Performance test results

[0084] From the performance test results in Table 2, it can be seen that the self-healing long-lasting anti-corrosion coating material prepared in the present application not only performs well in mechanical properties, self-healing ability, corrosion resistance and environmental stability, but also shows good control in terms of release rate.

[0085] Analysis of Examples 1 to 7 shows that: Example 1 uses a single nanofiller. Although its performance is slightly inferior to other examples, it is still better than the comparative example. Specifically, the tensile strength and elongation at break are low, the repair efficiency and repair time are also slightly poor, the salt spray test and corrosion rate are slightly higher, the heat aging test time is short, but the release rate is moderate. Compared with Examples 2 to 7: The use of compound nanofillers can significantly improve the comprehensive performance of the coating material. The compounding of nanofillers not only improves the mechanical properties and self-repair ability of the coating material, but also enhances the corrosion resistance and environmental stability. In addition, the release rate is also effectively controlled, indicating that the compound nanofiller can better exert a synergistic effect. The mechanical properties, self-repair ability and environmental stability of these embodiments have been significantly improved, mainly because the synergistic effect of nanocellulose and nanosilica enhances the multi-faceted performance of the coating material.

[0086] By comparing Examples 2 to 7, it can be seen that the comprehensive performance of Examples 2 to 5 is better than that of Examples 6 and 7. It can be seen that by further optimizing the ratio of nanocellulose and nanosilicon dioxide to 0.6 to 1.5:1, the comprehensive performance of the coating material is significantly improved. For example, the tensile strength of Example 3 reaches 41 MPa, the elongation at break reaches 255%, the repair efficiency is as high as 90%, the repair time is only 20 minutes, the salt spray test time is as long as 1450 hours, the corrosion rate is 0.05 mg / cm² / day, the heat aging test time is 1250 hours, and the release rate is 0.018 mg / cm² / h. These data show that optimizing the ratio of nanofillers to 0.6 to 1.5:1 can significantly improve the mechanical properties, self-healing ability and environmental stability of the coating material.

[0087] By comparing Example 1 with Comparative Example 1, although a single nanofiller is used in Example 1, its performance index is lower than that of Examples 2 to 7 using compound nanomaterials, but it is significantly better than Comparative Example 1, which shows that the addition of nanofillers can improve the comprehensive performance of the coating material to a certain extent. This is because the high specific surface area and surface activity of the nanofiller enable it to form physical crosslinking points in the coating material, thereby improving the mechanical strength and toughness of the coating material. In addition, the barrier effect of the nanofiller can effectively block the penetration of the corrosive medium and extend the service life of the coating material.

[0088] By comparing Comparative Examples 2 to 4, it can be seen that the synergistic effect of microcapsules and nanofillers has a significant effect on improving the self-repairing ability and protective function of coating materials. Although Comparative Example 2 contains microcapsules and nanofillers, compared with Example 2, its performance in tensile strength, elongation at break and corrosion resistance is slightly inferior, but its self-repairing ability is equivalent to that of Example 2, indicating that the effect of using bio-based polyurethane compounding is better. In addition, when Comparative Example 3 does not contain nanofillers, although it has a certain self-repairing ability, it performs poorly in other key properties such as corrosion resistance and thermal aging stability; when Comparative Example 4 does not contain microcapsules, although the mechanical properties are enhanced, it lacks an effective self-repairing mechanism. Compared with Comparative Example 2, Comparative Examples 3 to 4 show that although the use of microcapsules or nanofillers alone can improve specific properties, it cannot fully optimize the overall performance of the material. When microcapsules and nanofillers work together, they can not only give the coating material a certain self-repairing ability, ensuring that it can quickly restore its integrity and original protective function after being damaged, but also improve the mechanical properties of the coating material, thereby extending the service life of the material to a certain extent and improving its reliability in harsh environments. This may be because: the microcapsules contain repair agents, which break and release these repair substances to fill the cracks when the coating is damaged, such as cracks; and the nanofillers can not only enhance the mechanical properties of the entire composite material, but also promote more effective diffusion and curing of the repair agent during the repair process, thereby accelerating and optimizing the repair process at the cracks.

[0089] By comparing Example 2 with Comparative Examples 2 to 4, it can be further seen that the comprehensive performance of Comparative Examples 2 to 4 is significantly worse than that of Example 2. This is because: after adding bio-based polyurethane, it can be used in combination with microcapsules and nanofillers to promote each other, thereby significantly improving the various properties of the coating material. As an environmentally friendly polymer material, bio-based polyurethane itself has good mechanical properties and processability, which can enhance the strength and toughness of the polymer matrix, thereby improving the mechanical properties of the coating material. Its dynamic covalent bonds can be broken when subjected to external forces, and recombined after the external forces are removed to restore the integrity of the coating; when it is combined with microcapsules, the active functional groups in the bio-based polyurethane can react chemically with the repair medium released from the microcapsules, and can release the repair agent when the material is damaged, thereby realizing the self-repair function and improving the durability and service life of the material. At the same time, the introduction of nanofillers not only enhances the mechanical properties of the material, such as tensile strength and elongation at break, but also improves the thermal stability and corrosion resistance of the material, because the nano-scale particles can be evenly dispersed in the polymer matrix to form a tighter and more stable structure. In addition, nanofillers can also act as a physical barrier to prevent the penetration of moisture and corrosive media, further improving the protective performance of the material. The three together can not only significantly optimize the internal microstructure of the material, but also greatly enhance the bonding force between interfaces, so that the final coating material has excellent self-healing ability, mechanical properties, and resistance to environmental factors, thus achieving an excellent level in comprehensive performance.

[0090] By comparing Comparative Example 5 and Comparative Example 6, it can be seen that the combination of bio-based polyurethane and nanofiller has significant advantages in improving the corrosion resistance of the coating. Comparative Example 5 contains both bio-based polyurethane and nanofiller, and its corrosion resistance is significantly better than that of Comparative Example 6 containing only bio-based polyurethane. This combination not only enhances the mechanical strength and toughness of the coating, but also greatly improves its ability to resist corrosion, ensuring that the coating can maintain a good protective effect for a long time. The reason may be that the nanofiller can form a uniformly dispersed microstructure in the polymer matrix, effectively preventing the penetration of corrosive media, while enhancing the overall density and stability of the material. In addition, the nanofiller can also improve the interfacial bonding force of the bio-based polyurethane, further improving the durability and protective performance of the coating. Therefore, the synergistic effect of bio-based polyurethane and nanofiller not only optimizes the internal structure of the material, but also enhances the corrosion resistance of the coating.

[0091] By comparing Example 3 with Comparative Examples 5-6, it can be further illustrated that the comprehensive performance of the coating material in Example 3 is significantly better than that in Comparative Examples 5-6, which further confirms that the use of bio-based polyurethane, microcapsules and nanofillers at the same time can promote each other, thereby making the various properties of the coating material comprehensively and substantially improved. The reason may be that the presence of microcapsules enhances the effect of bio-based polyurethane and nanofillers. Bio-based polyurethane itself has good mechanical properties and environmental adaptability, and the introduction of microcapsules further optimizes these properties. Nanofillers are evenly dispersed in the polymer matrix to form a dense microstructure, effectively preventing the penetration of corrosive media and improving the overall corrosion resistance of the coating. The shell material of the microcapsule can be broken under specific conditions, thereby releasing the active substance inside, ensuring the continuous release of the repair agent within the required time, and improving the self-repair effect. In addition, the physical barrier formed by the microcapsules can control the diffusion rate of the active substance, slow down the release rate of the active substance, and make it evenly distributed in the coating, thereby achieving more effective self-repair.

[0092] Combining Examples 1 to 7 and Comparative Examples 1 to 7, the addition of bio-based polyurethane, microcapsules and nanofillers is unique and irreplaceable in improving the performance of the coating, and exhibits significant synergistic effects when used in combination. Nanofillers lay the foundation for the basic performance of the coating by enhancing the mechanical properties of the matrix and providing preliminary self-repairing capabilities. Bio-based polyurethane further enhances the self-repairing ability and corrosion resistance of the coating through its dynamic covalent bonds and active functional groups, enabling it to exhibit better protective performance in corrosive environments. Microcapsules further enhance the self-repairing ability and corrosion resistance of the coating by precisely controlling the release rate of active substances to ensure the durability and efficiency of the self-repairing effect. The synergistic effect of these three functional materials enables the coating to reach the optimal level in terms of mechanical properties, self-repairing ability, corrosion resistance and environmental stability, which is significantly better than the effect of using a single material or any combination of the two.

[0093] The inventors further discovered that the design of the microcapsules has a certain influence on the performance of the self-repairing long-lasting anti-corrosion coating material, and designed the following embodiment for analysis.

[0094] Taking Example 3 as an example, by changing the mass ratio of the core material to the wall material in the microcapsule, Examples 8 to 11 were obtained, and the above performance analysis was performed. The mass ratio of the core material to the wall material and the test results were recorded in Table 3 below.

[0095] Table 3 Mass ratio and test results

[0096] It can be seen from Table 3 that when the mass ratio of the core material to the wall material is in the range of 1:1 to 3:1, the comprehensive performance of the coating is better, and when the mass ratio is 2:1, the various performance indicators of the coating are the best. This may be because within this range, the ratio of the core material to the wall material is relatively balanced, which can not only ensure sufficient repair agent content, but also ensure that the thickness of the wall material is moderate, thereby achieving the best balance between mechanical properties, self-repair ability and release rate. When the mass ratio of the core material to the wall material is 4:1, there is too much core material and too little wall material, resulting in the wall material being unable to effectively protect the repair agent, and the repair agent is released prematurely, affecting the self-repair effect and durability. When the mass ratio of the core material to the wall material is 1:2, there is too much wall material and too little core material, resulting in insufficient repair agent content, and the self-repair efficiency and repair time are affected.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-repairing long-lasting anti-corrosion coating material, characterized in that: The material comprises the following raw materials by weight: 50-70 parts of bio-based polyurethane, 10-20 parts of microcapsules, 5-15 parts of nanofillers and 5-10 parts of additives; The microcapsule uses an isocyanate mixture as a core material and hexamethylene diisocyanate as a wall material. The isocyanate mixture includes a prepolymer generated by the reaction of lignin and hydrogenated xylylene diisocyanate and excess hydrogenated xylylene diisocyanate in the reaction.

2. The self-repairing long-lasting anti-corrosion coating material according to claim 1, characterized in that: The bio-based polyurethane is a plant oil-based polyurethane.

3. The self-repairing long-lasting anti-corrosion coating material according to claim 1, characterized in that: The average particle size of the microcapsules does not exceed 10 μm, and the shell thickness is 1.2 ± 0.25 μm; In the microcapsule, the mass ratio of the core material to the wall material is 1:1 to 3:1; In the isocyanate mixture, the mass ratio of the lignin to hydrogenated xylylene diisocyanate is 1:1.5 to 1:

2.

4. The self-repairing long-lasting anti-corrosion coating material according to claim 1, characterized in that: The average particle size of the nanofiller is 10-100 nm, and the nanofiller is selected from nanocellulose and / or nanosilicon dioxide.

5. The self-repairing long-lasting anti-corrosion coating material according to claim 4, characterized in that: The nano filler is a mixture of nano cellulose and nano silicon dioxide in any ratio.

6. The self-repairing long-lasting anti-corrosion coating material according to claim 5, characterized in that: The mass ratio of the nano-cellulose to the nano-silicon dioxide is 0.6-1.5:

1.

7. The self-repairing long-lasting anti-corrosion coating material according to claim 1, characterized in that: The auxiliary agent, calculated by weight, includes 1 to 3 parts of ultraviolet absorber, 1 to 3 parts of antioxidant and 1 to 4 parts of plasticizer.

8. A method for preparing the self-repairing long-lasting anti-corrosion coating material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: Step 1: Preparation of microcapsules Under stirring conditions, prepolymerizing lignin and hydrogenated xylylene diisocyanate according to a mass ratio at 80-90° C. to obtain an isocyanate mixture, and after cooling, adding hexamethylene diisocyanate to the isocyanate mixture to obtain an oil phase; adding the oil phase to an aqueous solution of a surfactant under an ice bath, stirring to obtain a stable emulsion, then adding an amine curing agent, heating to 40-60° C. and keeping the temperature for 2-4 hours, filtering, washing, and drying to obtain microcapsules; Step 2: Prepare coating materials The bio-based polyurethane, microcapsules, nanofillers and additives are sequentially mixed according to the mass fractions, stirred, filtered, and the coating material is prepared.

9. The method according to claim 8, characterized in that In step 2, the stirring process includes 10 to 20 minutes at 200 to 500 r / min and 30 to 60 minutes at 1000 to 2000 r / min.

10. Application of the self-repairing long-lasting anti-corrosion coating material according to any one of claims 1 to 7 in the fields of marine engineering, chemical equipment, building exterior walls and transportation.

Citation Information

Patent Citations

  • Urea-formaldehyde resin microcapsule formulations of herbicides sethoxydim and preparation method thereof

    CN101396018A

  • Self-repairing self-lubricating bifunctional anticorrosive coating and preparation method thereof

    CN109971311A

  • Wall damage self-repairing decorative paint and preparation method thereof

    CN110172300A

  • Double-shell self-repairing microcapsule, and preparation method and application thereof

    CN111790325A

  • Anticorrosion and antifouling integrated self-repairing microcapsule and preparation method thereof

    CN111925681A

Cited By

  • Flexible polymer antifouling tablecloth and preparation method thereof

    CN119931321A